Aggregated neutrophil extracellular traps resolve inflammation by proteolysis of cytokines and chemokines and protection from antiproteases. Issue 1 (21st August 2018) - Hahn, Jonas; Schauer, Christine; Czegley, Christine; Kling, Lasse; Petru, Lenka; Schmid, Benjamin; Weidner, Daniela; Reinwald, Christiane; Biermann, Mona H. C.; Blunder, Stefan; Ernst, Jürgen; Lesner, Adam; et al.
ABSTRACT: Papillon‐Lefèvre syndrome (PLS) is characterized by nonfunctional neutrophil serine proteases (NSPs) and fulminant periodontal inflammation of unknown cause. Here we investigated neutrophil extracellular trap (NET)‐associated aggregation and cytokine/chemokine‐release/degradation by normal and NSP‐deficient human and mouse granulocytes. Stimulated with solid or soluble NET inducers, normal neutrophils formed aggregates and both released and degraded cytokines/chemokines. With increasing cell density, proteolytic degradation outweighed release. Maximum output of cytokines/chemokines occurred mostly at densities between 2 × 10 7 and 4 × 10 7 neutrophils/cm 3 . Assessment of neutrophil density in vivo showed that these concentrations are surpassed during inflammation. Association with aggregated NETs conferred protection of neutrophil elastase against αl‐antitrypsin. In contrast, eosinophils did not influence cytokine/chemokine concentrations. The proteolytic degradation of inflammatory mediators seen in NETs was abrogated in Papillon–Lèfevre syndrome (PLS) neutrophils. In summary, neutrophil‐driven proteolysis of inflammatory mediators works as a built‐in safeguard for inflammation. The absence of this negative feedback mechanism might be responsible for the nonresolving periodontitis seen in PLS.—Hahn, J., Schauer, C., Czegley, C., Kling, L., Petru, L., Schmid, B., Weidner, D., Reinwald, C., Biermann, M. H. C., Blunder, S., Ernst, J., Lesner, A., Bäuerle, T., Palmisano, R., Christiansen, S., Herrmann, M., Bozec, A., Gruber, R., Schett, G., Hoffmann, M. H. Aggregated neutrophil extracellular traps resolve inflammation by proteolysis of cytokines and chemokines and protection from antiproteases. FASEB J. 33, 1401–1414 (2019). www.fasebj.org